Galang Batang Special Economic Zone: Downstreaming Strategy and Economic Transformation of Bintan - Haryani, Dwi; Oktaviani, Riri (Journal Governance Bureaucratic Review, 2026)
This study examines the Galang Batang Special Economic Zone as a strategic instrument for accelerating downstreaming-based economic transformation in Bintan, Kepulauan Riau Province, Indonesia. The main problem addressed in this article is the extent to which Galang Batang SEZ can move Bintan’s economy beyond dependence on raw-resource extraction, tourism, and service-based activities toward a more integrated industrial structure based on bauxite processing, alumina production, investment facilitation, and export-oriented value creation. The objective of this study is to analyze the role of Galang Batang SEZ in supporting mineral downstreaming, strengthening industrial infrastructure, generating local economic linkages, and contributing to sustainable regional transformation. This research uses a qualitative descriptive-analytical method based entirely on secondary data. The data were obtained from academic literature, government documents, official reports, statistical publications, policy documents, and credible online sources related to special economic zones, downstreaming policy, regional industrialization, and Bintan’s economic development. The data were analyzed through document review and content analysis by classifying information into strategic foundations, industrial infrastructure, value creation, regional economic effects, governance challenges, and sustainability risks. The findings show that Galang Batang SEZ has strong potential to become a downstreaming hub because it combines strategic maritime location, bauxite-processing orientation, investment incentives, industrial infrastructure, port connectivity, and export market access. The SEZ also has the potential to support employment creation, local business growth, economic diversification, and regional competitiveness. However, its long-term impact depends on the ability of policymakers and industrial actors to prevent enclave industrialization, strengthen local supplier participation, improve workforce skills, ensure environmental management, and build adaptive governance.